To find the constant of variation, we can use the relationship established by the direct variation formula:
\[ W_m = k \cdot W_e \]
where:
- \( W_m \) is the weight on the moon,
- \( W_e \) is the weight on Earth,
- \( k \) is the constant of variation.
From the problem, we know that:
- \( W_e = 300 \) pounds (weight on Earth),
- \( W_m = 48 \) pounds (weight on moon).
We can rearrange the formula to solve for \( k \):
\[ k = \frac{W_m}{W_e} \]
Now, substituting the known values:
\[ k = \frac{48}{300} \]
Calculating this gives:
\[ k = \frac{48 \div 12}{300 \div 12} = \frac{4}{25} \]
Thus, the constant of variation \( k \) is:
\[ \boxed{\frac{4}{25}} \]